Defence of the west - "Hart, B. H. Liddell" (London, 1950)
THIS book deals with the immediate problems of an effective "Defence of the West" and some basic problems of the human search for security against aggression. It may thus be worthwhile to explain why the book begins by dealing with the immediate past with some of the principal puzzles of World War II. My original intention was to summarise the investigation of these questions in a separate small book. But my publishers expressed a strong preference for incorporating it as Part I of this book, and of other friends whom I consulted the majority agreed with the publishers' view. I hope that they may be right in their judgment of readers' taste for while I cannot presume to gauge other people's taste, I have become convinced in my own experience of the value of the historical approach to current problems. In trying to solve such problems, or make forecasts, it has repeatedly proved helpful to get a projection from the past through the present into the future.
Keywords: International relations